(untitled) (Comprehensive Journal of Science, 2026)
Cross drain culverts are essential for managing surface runoff, preventing road erosion, and mitigating sediment impacts from forest roads on stream networks and surrounding ecosystems. This study aims to improve the design and spacing of cross drain culverts and to evaluate potential culvert locations using interactive Geographic Information Systems (GIS) tools. These tools enable the analysis of terrain features, hydrological networks, and sediment delivery volumes, facilitating accurate and informed design decisions. Results indicate that GIS-based approaches can reduce sediment accumulation and decrease maintenance and water management costs.